Freshwater Molluscs in Alimentary Canal of Molluscivorus Catfish Helicophagus leptorhynchus Ng and Kottelat, 2000 from the Chi River at Maha Sarakham Province, Northeastern Thailand - Tumpeesuwan, Sakboworn; Tumpeesuwan, Chanidaporn (Tropical Natural History, 2023)
The aim of this study is to investigate diversity of molluscs in the Chi River by alimentary canal content analysis of molluscivorous catfish Helicophagus leptorhynchus Ng and Kottelat, 2000, which were caught from the Chi River in Maha Sarakham Province. Nineteen species of freshwater molluscs were found in the alimentary canal contents of 85 H. leptorhynchus specimens. These fish were collected during October 2009 to September 2010 from the Chi River at Kantharavichai District, Maha Sarakham Province, Thailand. These molluscs comprise ten species of gastropods and nine species of bivalves. The highest frequency of occurrence of food items were 79.29% for Corbicula fluminea; whereas the second and the third were 35.29% for Limnoperna siamensis and 14.12% for Melanoides tuberculata, respectively. This result might be interpreted that this catfish feeds on both infaunal and epifaunal molluscs.